KALIGRAFI ISLAM PADA DINDING MASJID KUNA CIKONENG ANYER-BANTEN: KAJIAN ARTI DAN FUNGSI - Lia Nuralia (Berkala Arkeologi, 2017)
The aim of this paper is to understand the meaning and function of Islamic calligraphy (Arabic calligraphy) on the walls of the Cikoneng ancient mosque, Anyer-Banten. Descriptive with interpretation method is used to make the systematic description. Islamic calligraphy is found on the upper walls of the Cikoneng mosque inside the men's and the women's prayer room, consist a quotations of the Holy Qur'an and the Hadist of the Prophet. The conclusion is that Islamic calligraphy as decoration contains meaning and function through nonverbal language, which is adapted to the social conditions of Cikoneng society in the Dutch era.